Integration of RRBS and RNA-seq unravels the regulatory role of DNMT3A in porcine Sertoli cell proliferation - Xu, Dong; Yan, Saina; Jin, Huimin; Chen, Chujie; Tang, Xiangwei; Wang, Xu; Li, Yonghong; Fei, Fang; Yang, Anqi (Frontiers in Genetics, 2024)
DNMT3A participates in de novo methylation, yet its impact on the proliferation of testicular Sertoli cells remains unclear. Development-specific methylation has been proven to be associated with cellular development. Therefore, in this study, we simulated DNMT3A expression pattern during testicular development by DNMT3A interference. Then, RRBS and RNA-seq were used to decipher DNMT3A regulatory mechanisms on Sertoli cell proliferation. Immunofluorescence staining revealed the expression of DNMT3A in the Sertoli cells of the prepubertal testis. DNMT3A was demonstrated to inhibit the cell cycle and proliferation of Sertoli cells, while promoting cell apoptosis. After transfected with DNMT3A interference, a total of 560 DEGs and 2,091 DMGs produced by DNMT3A interference were identified between two treated groups, respectively. Integrating the results from RRBS and RNA-seq, the overlapping genes between DMGs and DEGs were found to be enriched in the Gene Ontology (GO) terms related to cellular development and the Apelin signaling pathway. The present study demonstrated the impact of DNMT3A on the proliferation of porcine testicular Sertoli cells, suggesting that DNMT3A primarily acts through the Apelin signaling pathway. These findings provide valuable insights into how DNMT3A influences testicular development and health, offering new perspectives.